Evaluation and Optimization of Microdrop Digital PCR for Detection of Serotype A and B Clostridium botulinum - Gao, Pengya; Wu, Changde; Zhang, Jin; Wang, Shuping; Huang, Ying; Dong, Yinping; Liu, Tingting; Ye, Changyun; Xu, Xuefang; Xin, Wenwen (Frontiers in Microbiology, 2022)
Clostridium botulinum is the causative pathogen of botulism. Laboratory detection of C. botulinum is essential for clinical therapy treatment of botulism due to the difficulty in diagnosis especially in infant botulism. The extreme toxicity of botulinum neurotoxin (BoNT) requires a sensitive detection method. Due to the detection limit of real-time quantitative PCR (q-PCR), a more sensitive detection method, micro-drop digital PCR (ddPCR) was applied in C. botulinum main serotypes A and B. The following performance criteria were evaluated by ddPCR: analytical sensitivity; repeatability; and diagnostic specificity. The limit of detection (LOD) was 0.84 and 0.88 copies/μl for BoNT A and B gene respectively by ddPCR with high specificity compared to 5.04×102 and 6.91×102 copies/µl by q-PCR. It was increased 10 times compared with q-PCR in spiked stool samples. This improvement in sensitivity was especially important in clinical samples as more positive samples were detected by digital PCR compared to q-PCR and two negative samples were identified by ddPCR. Meanwhile enrichment time for low bacteria content samples was shortened by four hours both in serotypes A and B C. botulinum by ddPCR compared with q-PCR, which are important for laboratory diagnosis and epidemiology work.